Notation of Uzbek Folk Music and Traditional Forms of Music in SIBELIUS Program - Usmanova Shahnoza Lutfillayevna (International Journal on Orange Technologies, 2021)
This article focuses on working with Sibelius music editor, one of the leading programs for creating and processing music documents and music information. There are currently several versions of the Sibelius program. They complement each other and differ in the introduction of some new features. We need to focus on the most commonly used versions of the program - Sibelius 4 and Sibelius 6.